Pengaruh Bagi Hasil, Kelompok Acuan, Kepercayaan Dan Budaya Terhadap Minat Menjadi Nasabah Bank Syariah - Gicella Fanny Andriani1; Halmawati Halmawati (Universitas Negeri Padang, 2019)
This research aims to determine whether profit sharing, reference groups, beliefs and culture have a significant influence on the interest in being a customer of Islamic banks partially or simultaneously. A total of 95 questionnaires were returned with complete and processed conditions. By using multiple regression techniques, the results of the study show that profit sharing and reference groups do not affect the interest in becoming a customer of Islamic banks. Trust has a positive influence on the interest in becoming a customer of Islamic banks. The higher the level of trust in the bank, the higher the customer will invest funds in the bank. In addition, the culture has a positive influence on the interest of being a customer of Islamic banks, the stronger a person's culture, the interest in becoming a customer of Islamic banks will increase..